Phytoconstituents as photoprotective novel cosmetic formulations - S., Saraf; C. D., Kaur (Pharmacognosy Reviews, 2010)
Phytoconstituents are gaining popularity as ingredients in cosmetic formulations as they can protect the skin against exogenous and endogenous harmful agents and can help remedy many skin conditions. Exposure of skin to sunlight and other atmospheric conditions causes the production of reactive oxygen species, which can react with DNA, proteins, and fatty acids, causing oxidative damage and impairment of antioxidant system. Such injuries damage regulation pathways of skin and lead to photoaging and skin cancer development. The effects of aging include wrinkles, roughness, appearance of fi ne lines, lack of elasticity, and de- or hyperpigmentation marks. Herbal extracts act on these areas and produce healing, softening, rejuvenating, and sunscreen effects. We have selected a few photoprotective phytoconstituents, such as curcumin, resveratrol, tea polyphenols, silymarin, quercetin and ascorbic acid, and have discussed the considerations to be undertaken for the development of herbal cosmetic formulations that could reduce the occurrence of skin cancer and delay the process of photoaging. This article is aimed at providing specifi c and compiled knowledge for the successful preparation of photoprotective herbal cosmetic formulations.
Keywords: Antiaging phytoconstituents; botanical antioxidants; photoprotective herbs; ultraviolet radiations